(untitled) (Baghdad Science Journal, 2025)
This study included effect of polyherbs mixture treatment of diabetic patients type II for two months. The polyherbs mixture contains Nigella sativa seeds, Boswellia carterri gum, Citrus aurantifolia fruits, Elettaria cardamomum fruits. Also this study included estimation of some biochemical parameters in the serum Diabetes Mellitus (D.M.) patients-type II and knowing the relationship of these parameters with this disease. The parameters are glucose, cholesterol ,High density , Low density lipoproteins( HDL-C, LDL-C) respectively , Triglycerides TG, urea, total protein , albumin , Alkaline phosphatase ALP,Transaminase GOT, GPT enzymes . Take (77) samples of diabetic patients serum type II which included (47) samples for group one: herbs + chemical treatment (drugs), (30) samples for group two: herbs only which were compared with (30) samples from health person as control group. From this study, the results shows that is an increase in the value of the following parameters such as glucose, cholesterol, LDL-C, TG, urea, and enzyme ALP, GOT and GPT in blood before the treatment of patients with herbs and decreasing of these values after treatment with herbs for both one & two months , but an increasing was noticed when the treatment of these patients was stopped. At the same time, the results shows a decrease in HDL-C, total protein, albumin values before treatment with herbs of these patients and an increasing after treatment but decreasing was noticed at stopping of the treatment. On the other hands, these results observed the level of cholesterol for second group of patients after treatment with polyherbs for first and second month return to normal level and LDL-C level of the two groups of patients and increasing of these levels after stopped the treatment for one month to a value approximately to the value before treatment of these patients. Also observed the levels of total protein, albumin reached to normal levels of these parameters for the second group of patients treatment at second month.